2013
DOI: 10.1590/s1020-49892013000500009
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation for treating diarrhea in children: a systematic review and meta-analysis

Abstract: Galvao TF, Thees MFRS, Pontes RF, Silva MT, Pereira MG. Zinc supplementation for treating diarrhea in children: a systematic review and meta-analysis. Rev Panam Salud Publica. 2013;33(5):370-7. Suggested citationZinc supplementation for treating diarrhea in children: a systematic review and meta-analysis Results. Eighteen of 1 041 studies retrieved were included in the review (n = 7 314 children). Zinc was beneficial for reducing the duration of diarrhea in hours (mean difference [MD] = -20.12, 95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…These findings are in agreement with a previous randomized clinical trial testing the effect of daily oral zinc in diarrheic neonatal Holstein calves which, showed that ZM-treated calves had a numerically, though not significantly increased ADG compared to calves treated with zinc oxide or placebo due to small sample size [11]. In general, our trial findings are in agreement with the large body of human literature supporting the use of oral zinc for the prevention and treatment of diarrhea and impaired growth in children [5,10,33].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with a previous randomized clinical trial testing the effect of daily oral zinc in diarrheic neonatal Holstein calves which, showed that ZM-treated calves had a numerically, though not significantly increased ADG compared to calves treated with zinc oxide or placebo due to small sample size [11]. In general, our trial findings are in agreement with the large body of human literature supporting the use of oral zinc for the prevention and treatment of diarrhea and impaired growth in children [5,10,33].…”
Section: Discussionsupporting
confidence: 92%
“…Diarrhea during follow-up was the most commonly reported outcome assessed in this review. Numerous systematic reviews of therapeutic zinc on diarrheal outcomes have been conducted, all of which suggest some benefit [ 58 , 78 80 ]. The effects of zinc on diarrhea at a specified day of follow-up were recently summarized in a Cochrane review and pooled relative risks of diarrhea at day 3, day 5, and day 7 associated with zinc all showed a statistically significant benefit [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regards to zinc supplementation of ORS in children with acute diarrhoea, it has been shown to be beneficial in malnourished children [ 25 ] but has been poorly studied in well-nourished ones. The postulated mechanisms include improved absorption of water and electrolytes by the intestine [ 26 , 27 , 28 ], regeneration of gut epithelium [ 29 ], increased levels of enterocyte brush-border enzymes [ 30 ], and enhanced immunologic mechanisms. Therefore, WHO recommended early oral rehydration therapy and zinc supplementation to treat acute diarrhoea in children [ 1 ].…”
Section: Discussionmentioning
confidence: 99%